Differences between males and females in the prediction of smartphone use while driving: Mindfulness and income. (June 2020) - Kita, Erez; Luria, Gil
Highlights: Males who are high on mindfulness use their smartphones less while driving than do males who are low on mindfulness. Males with low incomes use their smartphones more while driving than do males with high incomes. Income and mindfulness are not related to the level of smartphone use by female drivers. Abstract: Introduction: This study examines the relationship between two variables–mindfulness and income–with regards to their relationship to the use of smartphones by young drivers, which has been known to increase the likelihood of car accidents, endangering young drivers and other road users. The study focuses on the relationship between these variables and the use of smartphones while driving, and how this relationship differs between males and females. Method: The study sample included 221 young drivers who were legally permitted to drive without supervision. The subjects were first asked to complete questionnaires on mindfulness and income. Next, their smartphone use while driving was monitored over a one-month period. This study is unique as it used an objective smartphone monitoring application (rather than self-reporting) to count the number of times the young participants actually touched their smartphones while driving. Results: The findings show that the effects of social and personal factors (i.e., income and mindfulness) on the use of smartphones while driving are significant for males but not for females. Conclusions: Most studies that investigate differences between males and females with respect to safety focus on differences in the averages of safety-related variables (such as safety performance and outcomes). In the current study, however, we identified differences in relationships between variables and demonstrated that what predicts safety-related behavior in males may not be a good predictor for females. Practical applications: Mindfulness and income can be used to identify male populations that are at risk of using smartphones while driving. Interventions that improve mindfulness can be used to reduce the use of smartphones by male drivers.